Re-Visionen des Politischen : Im Blickfeld - Jahrbuch der Hamburger Kunsthalle - Herding, Klaus; Hensel, Thomas; Gockel, Bettina; Stuffmann, Margret; Krystof, Doris; Uppenkamp, Bettina; Schmidt-Wulffen, Stephan; Warnke, Martin; Wagner, Monika; Zbikowski, Dörte; Hamburger Kunsthalle, Hamburg (Hamburg : Christians Verlag, 1998)
Gainsboroughs, Thomas ; Klein, Yves ; Sherman, Cindy ; Ernst, Max ; etc.
Duits
boek